Exiled and Convict: Workers and Working System in the Nutmeg Economy in Banda, 1850-1860 (History Department, Semarang State University and Historian Society of Indonesia, 2022)
Banda Islands had a particular landmark in the traffic of world trade history. These islands are recognized as green gold and became one of the main sources of colonial profit. At the peak of the nutmeg trade, the Dutch colonial government built massive perkens (nutmeg plantations). The development of these perkens had scratched a typical history line in Indonesia’s history of economy and colonialism. It created a new economic zone but also laid a dark markdown on the practice of slavery and the workforce on the island. Another consequence was creating a new hybrid social and cultural identity in Banda. This article examines the development of Banda as a new economic zone, the mobilization of workers, and its working system in the nutmeg economy during the colonial period. It argues that the use of exiles and convicts in the nutmeg economy was a colonial strategy to escape to a newly legal ordonnance that abolished the practice of slavery in the perkens. Kepulauan Banda memiliki landmark tertentu dalam lalu lintas sejarah perdagangan dunia. Pulau-pulau ini diakui sebagai emas hijau dan menjadi salah satu sumber utama keuntungan kolonial. Pada puncak perdagangan pala, pemerintah kolonial Belanda membangun perken (perkebunan pala) besar-besaran. Perkembangan perken ini telah menggores garis sejarah yang khas dalam sejarah ekonomi dan kolonialisme Indonesia. Ini menciptakan zona ekonomi baru tetapi juga memberikan penurunan harga gelap pada praktik perbudakan dan tenaga kerja di pulau itu. Konsekuensi lain adalah menciptakan identitas sosial dan budaya hibrida baru di Banda. Artikel ini mengkaji perkembangan Banda sebagai kawasan ekonomi baru, mobilisasi tenaga kerja, dan sistem kerjanya dalam perekonomian pala pada masa kolonial. Ia berpendapat bahwa penggunaan orang buangan dan narapidana dalam ekonomi pala adalah strategi kolonial untuk melarikan diri ke ordonansi hukum baru yang menghapuskan praktik perbudakan di perken. Cite this article: Barjiyah, U., Margana, S.(2022). Exiled and Convict: Workers and Working System in the Nutmeg Economy in Banda, 1850-1860. Paramita: Historical Studies Journal, 32(2), 171-179. http://dx.doi.org/10.15294/paramita.v32i2.32982